English Teacher’s Strategies in Delivering Materials Using E-Learning Application Before and Amid Pandemic at Smk N 2 Pariaman - Oktaviani, Melani; Imelwaty, Sri; Afriyanti, Rika (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This research was motivated by the use of e-learning applications that have been implemented by one of the vocational high schools in West Sumatra province, Indonesia since 2018. This aim of the study is to describe the strategies of English teacher in delivering learning materials both before the pandemic and during the covid-19 pandemic. The researcher uses a qualitative research with an autobiographic case study because the researchers want to describe the personal experience of a teacher. The qualitative data from the structured interviews were analyzed by using theory from (Khan, 2011)to classification the strategy in using e-learning application. The results of this study show that before and amid pandemic COVID-19, the English teacher’ strategies in delivering material through e-learning applications at SMK N 2 Pariaman have increased. The strategies used before the pandemic were presentation strategies and generative learning strategies. Meanwhile, amid a pandemic, teacher used presentation strategies, exhibitions, demonstrations, exercises and practices, tutorials, discussions, interactions, modeling, facilities, collaboration, generative learning and motivation. This change was possibly occurred because of the demands of the role of a teacher who must always deliver the learning materials to students even though they have to study online.